2022
DOI: 10.3389/fimmu.2022.961695
|View full text |Cite
|
Sign up to set email alerts
|

An ion-channel-gene-based prediction model for head and neck squamous cell carcinoma: Prognostic assessment and treatment guidance

Abstract: PurposeHead and neck squamous cell carcinoma (HNSCC) is a very diverse malignancy with a poor prognosis. The purpose of this study was to develop a new signature based on 12 ion channel genes to predict the outcome and immune status of HNSCC patients.MethodsClinicopathological information and gene sequencing data of HNSCC patients were generated from the Cancer Genome Atlas and Gene Expression Omnibus databases. A set of 323 ion channel genes was obtained from the HUGO Gene Nomenclature Committee database and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Ion channels, transmembrane proteins responsible for selective ion transport, play a critical role in regulating tumor cell behavior [ 43 45 ] and the TME [ 46 ]. Their widespread presence in cells makes them valuable indicators for cancer diagnosis, therapeutic targeting, and prognosis [ 47 ]. Therefore, the classification of CRC patients into subtypes based on ion channel gene expression holds significant study value, which was demonstrated by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channels, transmembrane proteins responsible for selective ion transport, play a critical role in regulating tumor cell behavior [ 43 45 ] and the TME [ 46 ]. Their widespread presence in cells makes them valuable indicators for cancer diagnosis, therapeutic targeting, and prognosis [ 47 ]. Therefore, the classification of CRC patients into subtypes based on ion channel gene expression holds significant study value, which was demonstrated by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The TCGA database, data sets GSE41613 (Han et al 2022 ; Liu et al 2023 ) and GSE127165 (Yan et al 2022 ) from the GEO database, and the clinical parameters of the HNSCC samples were downloaded and used to generate the normalized gene expression data. In addition, the combat function is used to eliminate batch effect differences between datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have made significant progress in establishing prognostic models for HNSCC to predict patient survival. These models have been constructed using various biological factors and gene sets, including immune-related long non-coding RNAs [ 14 ], immune infiltration-related genes [ 15 ], ferroptosis-related genes [ 16 ], N6 methyladenosine (m6A) regulator-related genes [ 17 ], and ion channel related genes [ 18 ]. These models, constructed using Lasso regression, have proven effectiveness in predicting patient survival rates, as well as the response to of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%